Putting Sustainable Investing into Practice: A Governance Framework for Pension Funds - Woods, Claire (Journal of business ethics, 2010)
This article presents a framework intended to provide pension funds with practical guidance for the successful implementation of a sustainable investing strategy. The framework is developed with respect to the UK and US pension funds (as these share certain common legal characteristics) and focuses on the changes that pension funds adopting such a strategy should make to their investment strategies and governance (particularly through the formulation and articulation of clear investment mission and strong investment beliefs). The article proceeds with a review of socially responsible investment (SRI) and more recent responsible investment (RI) literature, in the context of growing public awareness (but not necessarily understanding) of the concept of sustainability (“Literature review of SRI field: SRI, RI and sustainable investing” section). It then examines the literature on pension fund governance, arguing the need for more detailed practical guidance for funds moving towards sustainable investing, especially for those implementing a sustainable investing strategy (“Anglo-American pension fund governance” section). It presents the framework for the practical implementation of sustainable investing in the “Sustainable investing framework” section. Finally, we review the relevant Anglo-American legal backdrop, outlining how pension funds adopting our framework should approach their fiduciary obligations, and then discussing potential regulatory enablers of sustainable investment (“Legal context: barriers to and enablers of sustainable investing” section).